Penapisan Cendawan Laut sebagai Agens Pengendalian Hayati Colletotrichum acutatum pada Tanaman Cabai - Syam, Nur Asmasari; Tondok, Efi Toding; Tarman, Kustiariyah; Widodo, Widodo (Jurnal Fitopatologi Indonesia, 2022)
Screening of Marine Fungi as Biological Control Agent of Colletotrichum acutatum on Chili Anthracnose is an important disease of red chili plants in Indonesia caused by Coletotrichum acutatum. Anthracnose is a very detrimental disease because it reduces yields. This study aimed to obtain marine fungi that have the potency to inhibit the growth of C. acutatum and suppress anthracnose disease, as well as to identify the potential of marine fungal isolates as biological control agents. The biological control agents’ potency was determined based on screening results such as antagonist test and volatile organic compound (VOC) while suppression of anthracnose disease on chili was evaluated by measuring the incidence of disease and the diameter of anthracnose symptoms. The results showed that all marine fungal isolates had the potential to inhibit the growth of C. acutatum and produce VOC. All the isolates has also the capability to suppress the incidence of anthracnose in chilies. Four strains of marine fungal, i.e. 4145, B3st2, GN322, Z521. Based on analysis of nucleotide sequences, the Fusarium proliferatum 4145, Trichoderma harzianum B3st2, fungal endophyte GN322, and Fusarium solani Z521 can be used as biological control agents C. acutatum on chili.